Sensitivity of Melt Pool Dimensions and Keyhole to Laser Beam Diameter - N. Hassine; S. Chatti; M. Ben Slama; L. Kolsi (Annals of "Dunarea de Jos" University of Galati, Fascicle XII, Welding Equipment and Technology, 2021)
The laser powder bed fusion process has witnessed a huge interest in recent years since it has the potential to produce challenging shapes in a broad range of applications. The process parameters have a considerable effect on melt pool size and on the development of defect porosity. This paper predicts numerically the effect of a large range of laser beam diameters on melt pool dimensions and on the occurrence of porosity defects such as keyhole. A series of single beads of Inconel IN625 was made using various combinations of beam diameters, scan speeds, and laser powers. The use of a large diameter was more suitable rather than a small diameter as it ensures a large and shallow heat affected zone, thus decreasing the development of the keyhole defect. Our numerical results correlate satisfactorily with experimental finding from literature.